Service Components and Their Importance in Health Insurance Changes - Urban Šebjan; Majda Bastič (Naše gospodarstvo/Our economy, 2013)
This article examines the importance of components comprising the service complementary voluntary health insurance (CVHI). The multicomponent service research model was tested using structural equation modeling (SEM) with a sample of 300 Slovenian users of this service. The authors found that the CVHI service consists of five components to which users attach different importance. Users attach the highest importance to mode of payment of insurance premiums, additional insurance coverage, and the quality of insurance services. Very few CVHI users would change their health insurance company, and a significant difference exists between users who favor changing health insurance companies and those who do not, albeit only in the importance of public opinion. For other components, no significant differen- ces were found.